Hemopexin alleviates sterile inflammation in ischemia-reperfusion-induced lung injury - Nakagiri, Tomoyuki; Köhler, Nadine R.; Janciauskiene, Sabina; Neubert, Lavinia; Knöfel, Ann-Kathrin; Pradhan, Pooja; Ruhparwar, Arjang; Ius, Fabio; Immenschuh, Stephan (Frontiers in Immunology, 2024)
Pulmonary ischemia-reperfusion (IR) injury (IRI) plays a significant role in various lung disorders and is a key factor in the development of primary graft dysfunction following lung transplantation. Hemopexin (Hx) is the major serum scavenger protein for heme, which is a prooxidant and pro-inflammatory compound. In the current study, we hypothesized that Hx could confer beneficial effects in sterile inflammation induced by IR-mediated lung injury. To examine this hypothesis, we administered Hx in an experimental mouse model of unilateral lung IRI. Our results demonstrate that treatment with Hx alleviated histopathological signs of inflammation in ischemic lungs, as evidenced by a reduction in the number of infiltrating neutrophils and decreased levels of perivascular edema. In addition, thrombotic vasoocclusion in pulmonary blood vessels of IRI lungs was reduced by Hx. Immunohistochemical analysis revealed that Hx inhibited the up-regulation of heme oxygenase-1, which is an enzyme highly induced by heme, in ischemic lungs. Finally, Hx administration caused a decrease in the levels of circulating B-and CD8+ T-lymphocytes in the peripheral blood of mice with pulmonary IRI. These findings suggest that the serum heme scavenger protein Hx holds therapeutic promise in alleviating lung IRI-mediated sterile inflammation. Thus, Hx may represent a preemptive therapeutic approach in IR-related lung disorders such as primary graft dysfunction in lung transplantation.